Histomorphological Study of the Small Intestine of the European Starling (Sturnus Vulgaris) in Basrah Province - Thaer R. Mhalhal; Shaimaa Hameed Hassan; Majdy Faisal Majeed (University of Thi-Qar Journal of agricultural research, 2022)
Five European starlings (Sturnus vulgaris), which are necessary for this study, were procured from Basrah city. Two anatomical and histological studies were performed on each bird. Duodenum, jejunum, and ileum formed the small intestine's three parts. The ileum was short, the jejunum was large, and the duodenum was U-shaped. We will measure the weight and length, and calculate the ratio of length to weight for the small intestine/bird (IL/BL%) and (IW/BW%) . The small intestine has four tunicae; the mucosa covering with simple columnar cells with goblet cells, which has an oval shape. The mucosa layer descends in thickness from the duodenum to the ileum, whereas the goblet cells will be increased in number in the ileum than in the jejunum and duodenum. We note the difference in the lengths and diameters of the villi in the three parts , where the highest lengths are in the duodenum and the lowest in the ileum